Family Involvement in the Board of Directors: Effects on Sales Internationalization. (29th October 2012) - Sciascia, Salvatore; Mazzola, Pietro; Astrachan, Joseph H.; Pieper, Torsten M.
<x xml:space="preserve">Abstract</x> Previous research shows that family involvement in the board of directors can be both positive and negative for sales internationalization. The ambiguous nature of this relationship has hindered theory building on this important phenomenon. Integrating stewardship, stagnation, and upper echelons perspectives, we propose a nonlinear, J‐shaped relationship between family involvement in the board of directors and sales internationalization. Results from running ordinal regression analysis on data drawn from 203 U.S. family businesses confirmed our conjecture. We discuss the implications of our findings for family business theory and practice and indicate avenues for future research.